Kaiser Permanente's Farmers' Market Program: Description, Impact, and Lessons Learned - DeAnn Cromp; Allen Cheadle; Loel Solomon; Preston Maring; Elisa Wong; Kathleen M. Reed (Journal of Agriculture, Food Systems, and Community Development, 2016)
Farmers' markets are an innovative strategy to potentially increase healthy nutrition environments. Kaiser Permanente (KP), the largest private, nonprofit healthcare system in the country, has been hosting farmers' markets on its medical campuses since 2003 and now has markets in nearly 40 KP locations in four states: California, Hawaii, Oregon, and Maryland. This paper describes the KP farmers' market program and summarizes the results of a patron survey conducted in 2010 among 2,435 market patrons. The majority of patrons are KP physicians and staff, and a quarter of patrons are KP members and community residents. The markets appear to have an impact on what people are eating: 74% of all patrons reported eating more fruits and vegetables as a result of coming to the market. The KP experience may be generalizable to other healthcare organizations and to other large employers.